Climate induced thermocline aging and ventilation in the Eastern Atlantic over the last 32 000 years - Beisel, Elvira; Frank, Norbert; Robinson, Laura F.; Lausecker, Marleen; Friedrich, Ronny; Therre, Steffen; Schröder-Ritzrau, Andrea; Butzin, Martin (Paleoceanography and paleoclimatology, 2023)
The radiocarbon analysis of uranium-thorium-dated cold-water corals (CWCs) provides an excellent opportunity for qualitative reconstruction of past ocean circulation and water mass aging. While mid-depth water mass aging has been studied in the Atlantic Ocean, the evolution of the thermocline is still largely unknown. Here we present a combined 14C and 230Th/U age record obtained from thermocline dwelling CWCs at various sites in the eastern Atlantic Ocean, with intermittently centennial resolution over the last 32 ka. Shallow dwelling CWCs off Angola, located in the South Atlantic, infer a link between the mid-depth equatorial Atlantic and Southern Ocean. They confirm a 14C drawdown during the Last Glacial Maximum (LGM) and advocate for a consistent Southern Hemisphere radiocarbon aging of upper thermocline waters, as well as strong depth gradients and high variability. Direct comparison with 14C simulations carried out with an Ocean General Circulation Model yield good agreement for Angola. In contrast, the North Atlantic thermocline shows well-ventilated water with strong variations near the position of today's Azores Front (AF), neither of which are captured by the model. During the Bølling-Allerød, we confirm the important role of the AF in separating North and South Atlantic thermocline waters and provide further evidence of a 500 year long deep convection interruption within the Younger Dryas (YD). We conclude that the North and South Atlantic thermocline waters were separately acting carbon reservoirs during the LGM and subsequent deglaciation until the modern circulation was established during the YD.